Hubungan Usia dan Paritas Ibu Bersalin dengan Kejadian Partus Prematurus di RSIA Husada Bunda Kabupaten Kampar Tahun 2022 - Natasya, Lidiya; Arvan, Arvan; Apriyanti, Fitri (Evidence Midwifery Journal, 2023)
Preterm labor is the presence of uterine contractions accompanied by changes in the cervix before 37 weeks of gestation and can cause premature birth. Every year, it is estimated that 1 in 10 babies are born prematurely. Premature birth can cause serious complications including death. Premature birth is a problem with a high prevalence in the world. The aim of the research was to determine the relationship between the age and parity of the mother at birth and the incidence of premature parturition. This research method is quantitative with a Case Control design. The population of the case group was all mothers who experienced preterm labor, totaling 120 mothers and the control group of mothers who gave birth at term, totaling 920 mothers. The research samples were in 2 groups 1: 1, namely 120 cases and 120 controls. The case sample technique was taken using total sampling while the control group used systematic random sampling. Data analysis used univariate and bivariate with the chi-square test. The statistical test results showed that the p value = 0.000 (? 0.05), which means there is a relationship between the age and parity of the mother at birth and the incidence of premature parturition. It is hoped that pregnant women will always carry out routine antenatal care checks so that the risk of premature labor can be prevented and treated as early as possible